Nudging the Self-employed into Contributing to Social Security: Evidence from a Nationwide Quasi Experiment in Brazil - Mariano Bosch Mossi; Danilo Fernandes; Juan M. Villa (Inter-American Development Bank (IDB), 2015)
This paper studies the first large scale effort by the Brazilian government to increase the social security compliance of self-employed workers using behavioral interventions. In 2014, the Brazilian Ministry of Social Security gradually delivered by postal mail a booklet reminding nearly 3 million self-employed workers their obligation to contribute to social security. We find that, sending the booklet increased payments by 15 percent and compliance rates by 7 percentage points. This increase is concentrated around the month the booklet was delivered and disappears three months after the intervention, a pattern known as action and backsliding. The relatively brief increase in payments outweighs the cost of sending the booklet by at least a factor of 2. Our results suggest that active behavioral interventions could be used as policy instruments that are orders of magnitude more cost-effective than subsides to increase social security contributions in developing countries, particularly for the self-employed.
hdl:11319/7313
Keywords: D03; H26; H55; O17; 330; Behavioral interventions; Tax evasion; Informal Sector; Social Security and Pensions